Computational methodology for determination of yarn twist and diameter. Issue 11 (2nd November 2019) - Neckář, Bohuslav; Das, Dipayan
Abstract: In this article, a set of theoretical relations among yarn count, twist, and diameter is derived based on a simplified mechanics of fibre compression. It is found that the basic quantity that determines these relations in yarns is the fiber packing density. The theoretical results are found to be in good agreement with the experimental data. Also, how to use these relations for industrial production of yarns is demonstrated with the help of practical examples.